Testing scalable interventions to reduce conflict in the drylands - Veldhoven, Anouk; Rikken, Emma; Son, Hyuk; Morsink, Karlijn; Shikuku, Kelvin Mashisia; Haar, Lotte van der; Jensen, Nathaniel D. (Jameel Observatory for Food Security Early Action, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025